Merdeka Belajar Curriculum: A Study on EFL Teachers' Varying Expressions of Agency - Sonia Handini Lubis; Endang Fauziati; Dewi Rochsantiningsih (VELES Voices of English Language Education Society, 2023)
In Indonesia, the introduction of the new Merdeka Belajar curriculum emphasizes the significance of teachers’ agency, denoting their proactive role in influencing their professional conditions for the betterment of education. While agency is a pivotal aspect of teachers' professionalism, its recognition has become essential for the effective enactment of the new curriculum in classrooms. Despite the global surge in research on teacher agency, studies examining its variations among EFL secondary teachers in Indonesia, particularly in the context of the Merdeka Belajar curriculum, remain scant. This research employed a qualitative descriptive approach to explore these variations. Drawing on Jenkins' (2019) categorizations — proactive teacher agency, active teacher agency, and passive teacher agency — this study assessed the prevalent types of agencies in Indonesia. Furthermore, Bandura's (2001) core properties of agency were utilized to delve into the characteristics of proactive teacher agency in relation to the curriculum. The findings from this study offer valuable insights for pedagogical practices, providing policymakers with informed perspectives to facilitate successful curriculum transitions.